Development of pyramided lines with two resistance genes, Pish and Pib, for blast disease (Magnaporthe oryzae B. Couch) in rice (Oryza sativa L.) - Koide, Y.; Kawasaki, A.; Telebanco-Yanoria, M.J.; Hairmansis, A.; Nguyet, N. T. M.; Bigirimana, J.; Fujita, D.; Kobayashi, N.; Fukuta, Y. (Wiley, 2010)
With 2 figures and 4 tables Gene pyramiding is considered one of the most effective strategies for achieving durable resistance against blast disease (Magnaporthe oryzae B. Couch) in rice (Oryza sativa L.), although few studies have evaluated the combining effect of the resistance genes. We report the development of pyramided lines with two major blast resistance genes, Pish and Pib, and the evaluation of the combining effect of them. The two genes pyramided lines were selected from the progenies of a cross between one near isogenic line (NIL), which harbours Pish, and another NIL, which harbours Pib, in the genetic background of blast susceptible variety, CO 39. The presence of the resistance genes was confirmed by DNA markers linked to them. To obtain DNA markers for Pish, we genetically mapped the Pish locus. We confirmed the additive effect of Pish and Pib in the pyramided lines by their reaction patterns to blast isolates, suggesting the potential availabilities of the combinations of these genes. In addition, we provide DNA markers linked to Pish for marker aided selection in rice blast resistance breeding.